Penerapan Strategi Komunikasi Model Knowledge, Attitude, Practice Dalam Kegiatan Sosialisasi Undang-Undang Kepada Masyarakat Dusun Karangnongko Yogyakarta - Susilowati Susilowati (Program Pendidikan Vokasi Universitas Brawijaya, 2018)
Law no. 19 of 2013 socialization activity of on the Empowerment and Protection of Farmer conducted 2 (two) times a year at working visit recess time of Indonesian Member of Parliament. The implementation of communication strategy Cangara Knowledge model, Attitude, Practice as an effort to improve knowledge, attitude, and behavior of Karangnongko Villager Yogyakarta. The aim of this research is to determine implementation of communication strategies Knowledge model, Attitude, and Practice results made by the member of the Indonesian House of Representatives to socialize the law. The research is using descriptive method. There are three main stages in this research. They are: 1) target audience (audience), message, and channel; 2) message design planning, media production (draft), and pre-testing; 3) improvement of knowledge (knowledge), attitude (attitude) and behavior (practice) by considering some factors, that affect public in receiving some information. The results of this socialization in the form of knowledge (Knowledge) of society to Law no. 19 of 2013, the changing of behaviour (attitude) cognitive, affective, and public conatif and need public behavioral actions (Practice) after law socialization activities, conducted by the Member of the Indonesian House of Representatives A-363. Further evaluation needed from the socialization activities resul , to measure the success of socialization activities and it is also expected to do tit continuously (suistanable).